The perfection of believers and the access to God in the Letter to the Hebrews - Malheiros, Isaac (Vox Scripturae - Revista Teológica Internacional, 2017)
Perfection is the most controversial concept of the soteriology of Hebrews. The search for the meaning of τελειόω and cognate words in Hebrews is not limited to lexicological questions, but must take into account the theology of Hebrews. Through the method of bibliographical revision, and the exegetical and theological analysis of the concept of perfection, this article will make an assessment of the main interpretations of the concept of perfection in Hebrews, which will reveal that the position that interprets perfection as access to God fits more easily into the text and theology of Hebrews.